Fictive Scratching Patterns in Brain Cortex-Ablated, Midcollicular Decerebrate, and Spinal Cats - Aguilar Garcia, Irene Guadalupe; Dueñas-Jiménez, Judith Marcela; Castillo, Luis; Osuna-Carrasco, Laura Paulina; De La Torre Valdovinos, Braniff; Castañeda-Arellano, Rolando; López-Ruiz, Jose Roberto; Toro-Castillo, Carmen; Treviño, Mario; Mendizabal-Ruiz, Gerardo; Duenas-Jimenez, Sergio Horacio (Frontiers in Neural Circuits, 2020)
BACKGROUND The spinal cord central pattern generators (CPG) have been explained by symmetrical half-center hypothesis, the bursts generator, by computational models and more recently, connectome circuits. Asymmetrical models are conformed by extensor and flexor CPG modules at odds with the half-center paradigm. Other models include not only flexor and extensor motoneurons, but also motoneurons pools controlling biarticular muscles. It is unknown whether a preferred model can explain some particularities during fictive scratching (FS) in the cat. The first aim is to investigate the FS patterns considering the aiming and the rhythmic periods. A second objective is to examine the serotonin effects and segmental inputs on FS. METHODS The experiments were made in brain cortex ablated cats (BCAC), in the same cats after spinalization (SC) and in different midcolicular cats (MCC). Cats were immobilized and peripheral nerves were used to produce monosynaptic reflex and to modify the scratching patterns as well as for electroneurograms recording. RESULTS In BCAC, FS was produced by pinna stimulation and in some cases by serotonin. The scratching aiming phase (AP) initiates with the activation of flexor or extensor motoneurons. The application of serotonin during the AP produced simultaneous extensor and flexor bursts. Furthermore, WAY 100635 (5HT1A receptors antagonist) produced a very brief burst in the flexor tibialis anterior (TA) nerve followed by a reduction in its electroneurogram, whilst the soleus electroneurogram remained silent. In SC, rhythmic phase activity in the soleus motoneurons was recorded. Serotonin or WAY produced FS bouts. The electrical stimulation of Ia afferent fibres produced heteronimous monosynaptic reflexes waxing and waning during the scratch cycle. In MCC, FS began with flexor activity. Electrical stimulation of either deep peroneous or superficial peroneous nerves increased the duration of the TA electroneurogram. Medial gastrocnemius (MG) stretching or MG nerve electrical stimulation produced a reduction in the TA electroneurogram, and an initial MG extensor burst. Monosynaptic reflexes waxing and waning during the scratch cycle. CONCLUSION Descending pathways and segmental afferent fibres as well as serotonin and WAY produce changes on FS pattern. Half center hypothesis is more adequate to explain the central pattern generator in MCC.